Technology-Driven Interaction and English Language Learning Outcomes: The Mediating Effects of Engagement and Motivation - Hussain, Turab; Wilany, Eka; Putri, Aulia; Ria, Tiara Nove; Manuhutu, Natalia (Qualitative and Quantitative Research Center, 2025)
In the digital era, English language education is undergoing a profound transformation from traditional classrooms to smart learning environments driven by technology-based interaction. Understanding how technology-driven interaction (TDI) influences students’ learning success has become crucial in optimizing the effectiveness of modern English education. This study aimed to examine the direct and indirect effects of TDI on self-reported English learning outcomes (OUT) through the mediating roles of student engagement (ENG) and motivation (MOT). Using a quantitative design, data were collected from 300 English language learners in Pakistan and Indonesia through a structured online questionnaire and analyzed using structural equation modeling. The results revealed that TDI had a significant positive impact on both ENG and MOT, which in turn strongly influenced OUT. Moreover, both ENG and MOT significantly mediated the relationship between TDI and OUT, indicating that technology enhances learning outcomes primarily by increasing students’ engagement and motivation. These findings support theoretical frameworks such as Self-Determination Theory and the Community of Inquiry model, emphasizing the psychological mechanisms linking technology use to learning success. This study contributes to the growing body of research on technology-enhanced language learning by proposing a dual mediation model that explains how digital interaction translates into measurable academic achievement. Practically, the findings highlight the need to design technology-based English learning systems that foster engagement, sustain motivation, and enhance meaningful learning outcomes in smart educational environments.